2015
DOI: 10.1038/srep12257
|View full text |Cite
|
Sign up to set email alerts
|

Meshing complex macro-scale objects into self-assembling bricks

Abstract: Self-assembly provides an information-economical route to the fabrication of objects at virtually all scales. However, there is no known algorithm to program self-assembly in macro-scale, solid, complex 3D objects. Here such an algorithm is described, which is inspired by the molecular assembly of DNA, and based on bricks designed by tetrahedral meshing of arbitrary objects. Assembly rules are encoded by topographic cues imprinted on brick faces while attraction between bricks is provided by embedded magnets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Hacohen et al [26] demonstrated DNA-inspired patterned bricks with embedded magnets, self-assembling into a programmed structure, but report gravity bias. Stambaugh et al [27] reported self-assembled 2D structures of centimetersized spherical particles with internal magnets that were shaken vertically, and observed different resulting structures that were based on particle concentration and magnet shape.…”
Section: Introductionmentioning
confidence: 99%
“…Hacohen et al [26] demonstrated DNA-inspired patterned bricks with embedded magnets, self-assembling into a programmed structure, but report gravity bias. Stambaugh et al [27] reported self-assembled 2D structures of centimetersized spherical particles with internal magnets that were shaken vertically, and observed different resulting structures that were based on particle concentration and magnet shape.…”
Section: Introductionmentioning
confidence: 99%
“…The simulated results of these works show qualitative correspondence with experimental data obtained from systems of macroscopic particles. Among available options (Kudrolli, 2004;Kumar et al, 2015;Ojha et al, 2004), orbital shaking is a useful agitation method for macroscopic setups to study the dynamics and interactions of granular matter (Bhalla et al, 2014;Cademartiri et al, 2012;Grünwald et al, 2016;Hacohen et al, 2015;Tricard et al, 2013Tricard et al, , 2015. The statistics of the motion that orbital shaking imparts to solid, in-plane bound particles was however not characterised to date.…”
mentioning
confidence: 99%
“…Macroscopic self-assembly processes on a centimetre scale are dominated by twodimensional structures, where mechanical shaking is the most widely used source of disturbing energy. Hacohen et al (2015) demonstrated DNA-inspired patterned bricks with embedded magnets, self-assembling into a programmed structure, but report gravity bias. Stambaugh et al (2003) reported self-assembled 2D structures of centimetre-sized spherical particles with internal magnets that were shaken vertically, and observed different resulting structures that were based on particle concentration and magnet shape.…”
mentioning
confidence: 99%
See 2 more Smart Citations